Alpha fluctuations regulate the accrual of visual information to awareness. (February 2022) - Torralba Cuello, Mireia; Drew, Alice; Sabaté San José, Alba; Morís Fernández, Luis; Soto-Faraco, Salvador
Abstract: Endogenous brain processes play a paramount role in shaping up perceptual phenomenology. This is illustrated by the alternations experienced by humans (and other animals) when watching perceptually ambiguous, static images. We hypothesised that endogenous alpha fluctuations in the visual cortex pace the accumulation of sensory information leading to perceptual outcomes. Here, we addressed this hypothesis using binocular rivalry combined with visual entrainment and electroencephalography in humans (64 female, 53 male). The results revealed a correlation between the individual frequency of alpha oscillations in the occipital cortex and perceptual alternation rates experienced during binocular rivalry. In subsequent experiments we show that regulating endogenous brain activity via rhythmic entrainment produced corresponding changes in perceptual alternation rate. These changes were observed only in the alpha range but not at lower entrainment frequencies, and were much reduced when using arrhythmic stimulation. Additionally, entraining at frequencies above the alpha range did not result in speeding up perceptual alternation rates. Overall, these findings support the notion that visual information is accumulated via alpha cycles to promote the emergence of conscious perceptual representations. We suggest that models of binocular rivalry incorporating posterior alpha as a pacemaker can provide an important advance in the comprehension of the dynamics of visual awareness.